2001
DOI: 10.1067/mhn.2001.113941
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Tympanostomy Tube Sequelae

Abstract: Sequelae of tympanostomy tubes are common but are generally transient (otorrhea) or cosmetic (tympanosclerosis, focal atrophy). Nonetheless, the high incidence suggests a need for ongoing otologic surveillance of all patients with indwelling tubes and for a reasonable time period after tube extrusion. Long-term tubes should be used on a selective and individualized basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
394
7
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(464 citation statements)
references
References 11 publications
(15 reference statements)
31
394
7
22
Order By: Relevance
“…There are approximately 2.2 million episodes of OME diagnosed every year in the United States, causing expenses of nearly US$4 billion 4 . Currently, myringotomy with insertion of ventilation tubes is one of the two most common surgical procedures in NorthAmerican children and the main reason for children to take general anesthesia 5 . Even though considered a simple procedure with significant benefits, VT insertion may present undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately 2.2 million episodes of OME diagnosed every year in the United States, causing expenses of nearly US$4 billion 4 . Currently, myringotomy with insertion of ventilation tubes is one of the two most common surgical procedures in NorthAmerican children and the main reason for children to take general anesthesia 5 . Even though considered a simple procedure with significant benefits, VT insertion may present undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%
“…These sequelae include residual perforation of the tympanic membrane (TM), tympanosclerosis, segmental atrophy, retraction or retraction pocket, cholesteatoma, and hearing loss. 6,7 The extent to which these sequelae are attributable to M&T itself or to the middle-ear disease that prompted the procedure or to both has not been clear. Also unclear and the subject of controversy has been the extent to which the untoward sequelae of M&T might be offset by possible benefits in regard to children's later development.…”
mentioning
confidence: 99%
“…Among the various types of complications, tympanosclerosis and otorrhea generally present transient but common sequelae following VTI [73,74], with other studies reported permanent perforations and cholesteatoma [73,75,76]. As for the occlusion of grommets, infection, and the presence of granulation tissue, the evidence was too limited and blurred to determine the direction of effects between VTI and adverse events in CLP children with OME.…”
Section: Vti Versus Non-vtimentioning
confidence: 84%